Design and Performance Investigation of a Solar- Powered Biological Greywater Treatment System in the Iraqi Climate (Baghdad Science Journal, 2022)
The increase in population resulted in an increase in the consumption of water. The present work investigates the performance of a recycling solar- powered greywater treatment system for the purposes of irrigation, used to reduce the amount of waste grey water and reduce electricity consumption and reduce the costs of constructing large scale water treatment plants. The system consumes about 3814W per hour and provides water treatment about 1.4 m3 per day. The proposed system is designed to    residential, office and governmental buildings application. Tests are conducted in an office building at the Ministry of Science and Technology site in Baghdad. Laboratorial water samples testing analyses are conducted for measuring the COD, BOD5, TDS, NH4, NO3-TN, TOC, TSS, pH and oil and grease content according to the Iraqi standards. Test results revealed a huge decrease in the values of BOD5 and COD for readings for every15 days and for a period of 5 months by removing rate more than 90% and also noting the values of TOC by removing about 80%, this indicates that the results of Laboratory testing have proved the success of the treatment process.  The research is divided into two parts, theoretical and practical. The theoretical one includes choosing the type and size of the equipment and the required tools for the treatment system. While the practical one covers implementing a laboratory-scale system for the proposed treatment system and conducting experiments and laboratory analyses of greywater samples. Top of Form